The critically reflective practitioner - Thompson, Sue 1955-; Thompson, Neil 1955- (Bloomsbury Academic, 2023)
"This succinct and insightful guide to reflective practice is designed for students and practitioners across a range of professions in the human services - social work, healthcare and related fields. The third edition covers the ways in which pandemic-induced remote working has affected opportunities for spontaneous group reflection. It also includes new content which looks at the significance of reflective practice for management and leadership and clearer links across reflective learning, personal growth and spirituality"--Provided by publisher.